The interior plan concepts and exercises - Rengel, Roberto J. (Fairchild Books, 2023)
"The Interior Plan is an introductory-level text introducing students to the process of interior design space planning. Topics include the design of effective spatial sequences, functional relationships among project parts, arrangement of furniture, planning effective circulation systems, making spaces accessible, and designing safe environments with efficient emergency egress systems. Exercises throughout the book facilitate learning by encouraging students to apply ideas and concepts immediately after reading about them. In the third edition, the author expands on the evolution of design ideas and how they affect interior environments and the people who use them, thinking sustainably, and how interior elevations and reflective ceilings affect the plan"--